Attitude towards statistics among pre-service teachers of institute of teacher education - A A Mustam; M Adnan; J Johnny; M A B Setambah (Pascasarjana Universitas Pendidikan Indonesia, 2020)
universities and teacher training programs. The importance of this component of mathematics is essential to bettering one’s economic prospects, gaining employment, keeping employment, and obtaining better employment. The main objective of this study was to determine the attitude of pre-service teachers towards statistics. This study also aimed to investigate the relationship between attitude towards statistics with gender, major and campus respectively. The participants comprised of 80 undergraduates from the Institute of Teacher Education (IPG) who were enrolled in the preparatory programme for the bachelor’s degree in education; whereby, they need to undertake the Basic Statistics Course. They consisted of 3 main majors, namely, Malay Language; Physical Education and Health; and Design and Technology from two campuses which are Bahasa Melayu Campus and Temenggong Ibrahim Campus. The Survey of Attitudes toward Statistics (SATS 36) which was translated into Malay language and contains 36 items that assess six constructs (r=.827) was used to answer the main objective of this study. The study found that the attitude of pre-service teachers towards statistics were ranked medium (3.437). In order to address the second objective of this study, the Spearman correlation test using SPSS was employed to analyse the data collected through the SATS 36 questionnaire. The analyses indicated a very weak correlation between attitude toward statistics and gender (r=.048;p=.672), major (r=.153;p=.174) and campus location (r=.074;p=.514) respectively, which were not statistically significant. (Approx. 239 words).